Tajikistan : 2001 Article IV Consultation, First Review Under the Third Annual Arrangement Under the Poverty Reduction and Growth Facility; and Request for Waiver and Modification of Performance Criteria - Staff Report; Public Information Notice and News Brief; Statement on Behalf of the Authorities of Tajikistan. (IMF Staff Country Reports; Country Report ;, 2001)
As regards the performance under the third year arrangement, all performance criteria for end-December 2000 have been met, with the exception of the net domestic assets (NDA) target for the National Bank of Tajikistan (NBT). For several years, Tajikistan has been implementing an economic reform program intended to foster growth and poverty reduction through the development of the private sector and market-oriented mechanisms. Fiscal performance is satisfactory, but slippages in monetary policy have led to a surge in inflation and a sizable currency depreciation.